Pemanfaatan Kapur Padam dan Sedimen Danau Limboto Sebagai Bahan Dasar Penyusun Dinding Batu Bata - Hulop, Risrianto; Desei, Frice L.; Husnan, Rawiyah; Kadarningsih, Rahmani (Lambung Mangkurat University Press, 2024)
This study is based on knowing the compressive strength of bricks. The objectives that can be achieved are to analyze the characteristics of brick walls using lime, sedimentary soil and clay as well as conventional bricks and evaluate the comparative cost of making conventional bricks and lime-mixed bricks plus sedimentary soil. In this study, Data obtained from testing and analyzed quantitatively using appropriate statistical methods. This analysis will help in understanding the relationship between the composition of the mixture, the manufacturing process, and the characteristics of the resulting bricks. From the results of the analysis, the water absorption of bricks mixed with sedimentary materials, clay and lime. variation of sample 1, where the sample mixture (75% / 20% / 5%) water absorption is (29.72%) variation of sample 2, where the sample mixture (50% / 45% / 5%) water absorption is (9.45%) and Sample 3, (25% / 70% / 5%) water absorption is (9.22%). and clay bricks or without a mixture (100%) is (8.25%). This shows that the absorption capacity of mixed bricks of sediment, clay and lime materials which only have two variations 2 and 3. Meet the requirements of SNI 15-2094-2000 which requires a maximum water absorption capacity of 20% of bricks. While the average compressive strength comparison value of mixed bricks of sediment, clay and lime materials. sample variation 1, which sample mixture (75%/20%/5%) compressive strength value (13.6 kg/cm2) sample variation 2, (50%/45%/5%) which compressive strength value (19.8 kg/cm2) and sample 3, (25%/70%/5%) which compressive strength value (7.4 kg/cm2). and clay bricks without a mixture (100%) namely (36.4 kg/cm2). The compressive strength value of mixed bricks of sediment, clay and lime materials. Does not meet the minimum compressive strength requirements for building earthquake-safe houses (≥30).